2017
DOI: 10.1111/ecc.12783
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of qualitative evidence of cancer patients’ attitudes to mindfulness

Abstract: Mindfulness has been described as a non-elaborative, non-judgmental, present-centred awareness in which each thought, feeling or sensation is acknowledged and accepted. The aim of the present study was to systematically search and synthesise qualitative evidence of cancer patients' attitudes to mindfulness. A systematic review of qualitative evidence was conducted following the SPICE framework. All cancers were included. Medline, Cinahl, Science Direct, O-Alster and New Bank were searched from the first availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
24
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 23 publications
6
24
0
7
Order By: Relevance
“…This is in line with findings from a systematic review of qualitative evidence of attitudes to mindfulness of Caucasian cancer patients from an Anglo‐Saxon background . Similar to our study, the review found that patients often encountered challenges in engaging with mindfulness techniques, but such techniques can assist in the identification of coping strategies .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in line with findings from a systematic review of qualitative evidence of attitudes to mindfulness of Caucasian cancer patients from an Anglo‐Saxon background . Similar to our study, the review found that patients often encountered challenges in engaging with mindfulness techniques, but such techniques can assist in the identification of coping strategies .…”
Section: Discussionsupporting
confidence: 91%
“…Mindfulness‐based interventions (MBIs) have shown promising evidence to improve the mental well‐being of cancer survivors . A review of qualitative studies found that MBIs provided effective coping strategies to help people adjust to living with and beyond cancer and led to positive outcomes such as reduced stress and anxiety, making time, creating space, and increased spirituality . However, this evidence was mainly based on people from Anglo‐Saxon cultures like the United Kingdom, Canada, and Australia and did not inform on the appropriateness of MBIs from other cultures.…”
Section: Introductionmentioning
confidence: 99%
“…What do patients think of these approaches? Tate, Newbury-Birch, and McGeechan (2018) undertook and systematic review of qualitative evidence and found that patients often encounter challenges in engaging with mindfulness techniques, but such techniques can help in identifying coping strategies; importantly, mindfulness techniques need to accommodate individual patients' characteristics and perspectives.…”
Section: E D I T O R I a L "Yes I Have Cancer But I'm Also Lonely";mentioning
confidence: 99%
“…The call for better understanding the underlying mechanisms and processes of mindfulness practices has warranted the use of qualitative methodologies to explore cancer patient experiences and the effects of MBPs (Shennan et al 2011 ; Zimmermann et al 2018 ). Studies attempting to elucidate this have largely focused on women with breast cancer (Schellekens et al 2016 ; Tate et al 2018 ), with some exceptions (Kinner et al 2018 ; Mackenzie et al 2007 ). The majority of interventions followed the standard 8-week mindfulness-based stress reduction (MBSR) program (Kabat-Zinn 1990 , 2003 ; Tate et al 2018 ).…”
mentioning
confidence: 99%
“…Studies attempting to elucidate this have largely focused on women with breast cancer (Schellekens et al 2016 ; Tate et al 2018 ), with some exceptions (Kinner et al 2018 ; Mackenzie et al 2007 ). The majority of interventions followed the standard 8-week mindfulness-based stress reduction (MBSR) program (Kabat-Zinn 1990 , 2003 ; Tate et al 2018 ). However, several studies have used modified MBPs incorporating elements of mindfulness-based cognitive therapy (MBCT) (Chambers et al 2012 ) and acceptance commitment therapy (ACT) (Kinner et al 2018 ).…”
mentioning
confidence: 99%